PENDEKATAN TEOLOGI AGAMA-AGAMA TERHADAP RITUAL PONGONSONG BIHING DI SUKU SALUAN KRISTEN - Purnama Pasande; Jhon Efendi Bungalan; Elsye Evasolina Tulaka; Joddiar Septyanto; Desry Narliany Linggamo (Sekolah Tinggi Teologi Arastamar Bengkulu, 2025)
This article discusses the Pongonsong Bihing custom, a cultural practice of the Saluan tribe in Central Sulawesi performed in the context of death and the mourning period. This tradition arises from the belief that the spirit of the deceased can disrupt festivities if not honored through specific rites. Within the Christian Saluan community, this practice creates tension between ancestral traditions and Christian theological teachings regarding the state of the soul after death. Using a qualitative approach and a literature review, this article analyzes the Pongonsong Bihing custom based on a theological approach to religions. The study shows that although the aspect of belief in spirits conflicts with Christian doctrine, the social values such as respect, solidarity, and empathy within this custom can be accommodated ethico-theologically. This article also emphasizes that an inclusive approach to local culture can strengthen inter-religious harmony in Indonesia's multicultural society..